Diabetes meal planning & nutrition for dummies - Poole, Dr. Simon; Riolo, Amy; Rubin, Dr. Alan; Smithson, Toby (for dummies., 2024)
Learn how to eat well, improve your health, and enjoy life with diabetes The new edition of Diabetes Meal Planning & Nutrition For Dummies offers you a holistic approach to living your best life with diabetes. Optimize your diet and plan delicious meals that will empower you to take control, improve your health, prevent, and even reverse diabetes. Written by an award-winning chef and renowned doctor who are both experts in the field of nutrition, this book helps you understand what defines healthful eating for diabetes, its crucial role to long term health, and how meal planning is a key to successful diabetes management. Learn how to receive all the nutrients necessary for glucose control while managing Type 1 or Type 2 diabetes and maintaining ideal weight. Discover how to supercharge your diet and protect yourself from the complications associated with diabetes with anti-inflammatory and antioxidant-rich foods. To get you started, this indispensable guide includes 22 mouthwatering, easy to recreate, and affordable recipes that maximize the benefits of nutritious ingredients to regulate blood glucose levels. The kitchen and shopping hacks will enable you to master culinary therapy and take delight in preparing meals and cooking. This updated edition Diabetes Meal Planning & Nutrition For Dummies is an excellent resource for those interested in the latest diabetes-friendly nutrition guidelines, as well as anyone who has been diagnosed with diabetes or has a loved one who has been diagnosed, or would like to prevent it.